Renewal of Law Number 9 of 1961 Concerning Collection of Money or Object - Rendy Airlangga; Bertha Bernessa Sacharissa; Diana Septaviana (Sociological Jurisprudence Journal, 2024)
Indonesia consists of many existing communities, so it does not rule out the possibility of problems related to people's welfare. In order to overcome the social welfare that occurs, a philanthropic approach can be used, namely the love of humanity, in Indonesia philanthropic activities are regulated in Law Number 9 of 1961 concerning Collection of Money or Object, but over time the Act is deemed obsolete and necessary. to carry out reforms by paying attention to regulatory aspects related to licensing, fines, and supported by the existence of an independent institution that is accountable so that with the renewal of the Law it is hoped that in terms of philanthropic activities, it can play a greater role in improving the welfare of the community. The research in this study used a prescriptive normative research method. This study will describe the urgency of legal reform from Law Number 9 of 1961 concerning Collection of Money or Object and provide an overview of legal reform for philanthropy regulations in Indonesia.